Assessing Service-Learning in Community-Based Veterinary Medicine as a Pedagogical Approach to Promoting Student Confidence in Addressing Access to Veterinary Care - King, Erin; Mueller, Megan; Wolfus, Gregory; McCobb, Emily (Frontiers in Veterinary Science, 2021)
Community based veterinary medicine is a growing field and veterinary students need to be able to work with clients facing complex barriers to receiving veterinary care for their pet. Many veterinary clients experience challenges accessing veterinary care due to financial limitations, transportation access, language comprehension, the ability to comply to the care plan (e.g., disabilities, physical or mental health challenges, substance use), the ability to come to the clinic during the hours that it is open, and the ability to communicate outside of the appointment. The goal of this study was to assess student confidence levels working in accessible care before and after participating in a service-learning based community veterinary rotation. Results show significantly higher student confidence levels for every barrier after completing the Tufts at Tech (TAT) Clinical Rotation at Cummings Veterinary School of Medicine. Additionally, 86% (n = 85) of students strongly agreed or agreed that TAT affected their thoughts about community medicine and 77% (n = 76) strongly agreed or agreed that the rotation affected their feelings about underserved clients. Service-learning rotations in community based veterinary medicine could be one pedagogical approach in training veterinary students to work with a diverse clientele.